The gut-eye axis: the retinal/ocular degenerative diseases and the emergent therapeutic strategies - Kammoun, Sonda; Rekik, Mona; Dlensi, Aryj; Aloulou, Samir; Smaoui, Walid; Sellami, Sahla; Trigui, Khaled; Gargouri, Rahma; Chaari, Imen; Sellami, Hayet; Elatoui, Dhawia; Khemakhem, Nahed; et al. (Frontiers in Cellular Neuroscience, 2024)
The interplay between human microbiota and various physiological systems has garnered significant attention in recent years. The gut microbiota plays a critical role in maintaining physiological homeostasis and influences various aspects of human health, particularly via the gut brain axis. Since 2017, the challenging concept of the gut-retina axis has emerged thanks to a network analysis emphasizing the potential role of the gut microbiota disruption in the development of the age-related macular degeneration and further retinal damages. Many other ocular disorders have been linked to the dysbiosis of the gut microbiota, including uveitis and glaucoma. It has been shown that age related macular degeneration can be prevented or reversed using a diet that induces changes in the gut microbiota. The potential link between the gut microbiota as well as others types of microbiota such as the ocular surface microbiota and the development/progression of age related as well as inherited retinal degenerations and other degenerative eye diseases, has recently been broadened. Therefore, the pathogenesis of several eye diseases has recently been associated with a larger perception called the gut eye axis. This mini-review examines the potential mechanisms underlying the gut eye axis and suggests implications for the management of eye diseases. By understanding the modulation of the gut microbiota and its impact on eye disease, this mini-review provides insight into potential therapeutic interventions and avenues for future research.